Deskripsi Masalah Diri Siswa dan Implikasinya terhadap Bimbingan dan Konseling - M. Harwansyah Putra Sinaga; Nurul Syafitri Alwi; Siti Aisah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
This study aims to determine the students' self-problems experienced at Madrasah Tsanawiyah Negeri 2 Medan and their implications for Guidance and Counseling. This research method is a quantitative description with a survey research design. The subjects involved in this study were 62 students from grades VII-2 and VII-5 at Madrasah Tsanawiyah Negeri 2 Medan in Medan City. The data collection method used the General AUM Format 2 Junior High School questionnaire. The use of General AUM aims to determine the level of student problems, especially in the field of personal self. The problems experienced by students vary greatly for each individual, this is also experienced by class VII students at MTsN 2 Medan. A problem is a situation or condition experienced by a person that has not been resolved, making it difficult for a person to achieve his goals. From the research conducted, the results obtained are that the majority of students experience carelessness or carelessness; timid, shy or easily confused; considered stubborn by others; low self-esteem or lack of confidence; and irritable Keywords: Problems; Students; Implications of Counseling Guidance